Spiritual Values in Emha Ainun Nadjib's Charismatic Leadership in Maiyah Congregation - Wicaksono , Wahyu Widhi; Khuzaini; Soewitho (International Journal of Science and Society, 2024)
Leadership is integral to human capital development within organizations. This study investigates the charismatic spiritual leadership of Emha Ainun Nadjib in Jamaah Maiyah, a community he has nurtured for three decades with a fluid, self-sustaining organizational structure. Through a qualitative phenomenological approach, this research delves into Emha Ainun Nadjib's leadership, drawing from interviews with his close associates and Jamaah Maiyah members, complemented by data from observations, texts, and videos. The findings reveal Emha Ainun Nadjib's innate leadership abilities, shaped by his lifelong journey and grounded in Islamic principles and the life of Prophet Muhammad. Emha Ainun Nadjib embodies several traits of charismatic leadership, including personal charisma, vision, exceptional oratory skills, courage, empathy, and the ability to inspire and position himself relative to his audience. His leadership style emphasizes influence rather than authority, inspiring Jamaah Maiyah members through his thoughts, conduct, and charisma. The study underscores the significance of ethical leadership rooted in spiritual values, highlighting the potential of religion to foster effective leadership. However, it acknowledges limitations in confirming the broader application of Emha Ainun Nadjib's leadership beyond his immediate circle and Jamaah Maiyah.